Genetic variants associated with subjective well-being, depressive symptoms, and neuroticism identified through genome-wide analyses - Okbay, Aysu; Baselmans, Bart M L; De Neve, Jan-Emmanuel; Turley, Patrick; Nivard, Michel G; Fontana, Mark Alan; Linnér, Richard Karlsson; Gratten, Jacob; Buchwald, Jadwiga; Cavadino, Alana; Frazier-Wood, Alexis C; Furlotte, Nicholas A; et al. (IDEAS Working Paper Series from RePEc, 2016)
Daniel Benjamin, Meike Bartels, Philipp Koellinger and colleagues report a genome-wide association meta-analysis of subjective well-being, depressive symptoms and neuroticism. The study leverages a large sample size together with genetic correlations between the phenotypes to identify, with high confidence, loci associated with each phenotype. Very few genetic variants have been associated with depression and neuroticism, likely because of limitations on sample size in previous studies. Subjective well-being, a phenotype that is genetically correlated with both of these traits, has not yet been studied with genome-wide data. We conducted genome-wide association studies of three phenotypes: subjective well-being ( n = 298,420), depressive symptoms ( n = 161,460), and neuroticism ( n = 170,911). We identify 3 variants associated with subjective well-being, 2 variants associated with depressive symptoms, and 11 variants associated with neuroticism, including 2 inversion polymorphisms. The two loci associated with depressive symptoms replicate in an independent depression sample. Joint analyses that exploit the high genetic correlations between the phenotypes (| ρ ^| ≈ 0.8) strengthen the overall credibility of the findings and allow us to identify additional variants. Across our phenotypes, loci regulating expression in central nervous system and adrenal or pancreas tissues are strongly enriched for association.